Carry on and cross your fingers: a psycholinguistic approach to phrasal verbs and idioms in English - Wisintainer, Danielle dos Santos (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2022.